1993
DOI: 10.1177/026835559300800103
|View full text |Cite
|
Sign up to set email alerts
|

Physical Examination, Doppler Ultrasound and Colour Flow Duplex Scanning: Guides to Therapy for Primary Varicose Veins

Abstract: Objective: To compare physical examination (PE) and continuous-wave hand-held Doppler (CWD) examination with colour flow duplex scanning as a gold standard for greater saphenous vein (GSV) reflux. Design: Prospective performance of PE and CWD by two clinical examiners and subsequent duplex scanning by two vascular laboratory technicians unaware of the results of the PE and CWD examinations. Tapes were then reviewed; results of the duplex scanning were compared with physical and CWD findings. Patients: Thirty-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
1

Year Published

1995
1995
2004
2004

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 13 publications
1
27
1
Order By: Relevance
“…It demonstrates incompetence at the saphenofemoral junction but not incompetence through the sapheno-femoral junction. The limitations of continuous-wave Doppler are well know; assumptions based on Doppler findings may be inaccurate to a certain extent, because of lack of visualization and localization [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…It demonstrates incompetence at the saphenofemoral junction but not incompetence through the sapheno-femoral junction. The limitations of continuous-wave Doppler are well know; assumptions based on Doppler findings may be inaccurate to a certain extent, because of lack of visualization and localization [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Should preoperative duplex be a routine examination, or is it more conveniently limited only to cases the surgeon believes are not adequately diagnosed by clinical and CW Doppler examinations? In a well‐designed study duplex has been shown to correct clinical and CW Doppler diagnosis and modify the surgical procedure in more than 50% of cases 4 . But even if that figure were much lower, there are hardly arguments for operating one's veins without first looking at them.…”
Section: Discussionmentioning
confidence: 99%
“…Duplex evaluation of varicose veins was first reported in 1986, 2 and by 1991 it replaced phlebography completely in some leading centers 3 . Although later reports also suggested that varicose vein surgery “appears best guided by color flow duplex scanning,” 4 routine use of duplex prior to surgery seems not yet to be a well‐established practice. In a 1994 survey in the US, 18% of vascular technologists did not use duplex for vein mapping, and another 37% did so only occasionally, 5 while in a 1995 British survey only 33% of vascular and 15% of general surgeons used duplex for preoperative evaluation 6 …”
mentioning
confidence: 99%
“…The most accurate test was the tourniquet + HHD (sensitivity, 0.90; specificity, 0.45). More recently, DePalma et al 3 looked at the accuracy of clinical tests (cough test, tap test) and HHD for diagnosing saphenofemoral incompetence. Reflux was identified by duplex scanning, and subsequently confirmed operatively.…”
Section: Jr Novellmentioning
confidence: 99%